Electrochemical determination of paracetamol and chlorpheniramine using AuNPs-rGO modified glassy carbon electrode - Huynh Van Chung; Nguyen Hai Phong; Dao Thi Cam Minh; Ho Xuan Anh Vu; Pham Khac Lieu; Nguyen Thi Thanh Huyen; Trinh Ngoc Dat; Doan Manh Dung; Do Thi Duyen; Dinh Quang Khieu (Journal of Electrochemical Science and Engineering)
One of the significant durability challenges is the corrosion of reinforced concrete. A gold nanoparticle/reduced graphene oxide modified glassy carbon electrode (AuNPs-rGO-GCE) was fabricated using an electrochemical reduction method for the simultaneous determination of paracetamol (PAR) and chlorpheniramine maleate (CPM). AuNPs-rGO modified GC electrodes were prepared through direct electrochemical reduction of GO to rGO, followed by direct reduction of Au ions to Au on the rGO matrix. X-ray diffraction, scanning electron microscopy, Fourier-transform infrared spectra, Raman spectroscopy, energy dispersive X-ray spectroscopy, high-resolution transmission electron microscopy, electrochemical impedance spectroscopy, and X-ray photoelectron spectroscopy characterized the resulting AuNPs-rGO. It was found that AuNPs around 15.4 nm were highly dispersed on the rGO. The modification of GCE by AuNPs-rGO accelerates the electron transfer process and increases the conductivity of the electrode. The AuNPs-rGO modified electrode was used to simultaneously determine PAR and CPM using the square-wave anodic stripping voltammetry (SQW-ASV) method. Under suitable experimental conditions, the SQW-ASV method using AuNPs-rGO-GCE showed a wide linear range from 23.7 µM to 140 µM for PAR and from 7.5 µM to 54 µM for CPM. The limit of detection of PAR and CPM was 7.12 µM and 2.54 µM, respectively. The proposed SQW-ASV method was applied to analyze PAR and CPM in samples of herbal medicine simultaneously, and the results were compared with those of high-performance liquid chromatography, with no statistical difference.